Chronic Lymphocytic Leukemia: A Rare Cause of Pathological Fracture of the Femur - Parita Soni MD; Nidhi Aggarwal MD; Anand Rai MD; Vivek Kumar MD; Kamholz Stephan MD; Yoon Taek MD; Kupfer Yizhak MD (SAGE Publishing, 2017)
The incidence rate of chronic lymphocytic leukemia (CLL) in the United States is approximately 0.005%; men are at slightly higher risk than women. Bony involvement or pathological fracture rarely occurs in CLL, and it may be the initial presentation. An 85-year-old woman presented with acute respiratory failure secondary to pneumonia. Symptomatology included dyspnea. She was found to have pathological fracture of the femur caused by CLL. The diagnosis of CLL had been made 6 years previously, but the patient had refused therapy. On admission, the patient required endotracheal intubation, mechanical ventilation, and admission to the medical intensive care unit. Endotracheal intubation extubation was successful after 48 hours. The patient then complained of severe left knee pain. Bone radiograph and femoral computed tomography scan revealed acute pathological fracture of the left distal femur. There was no history of trauma. The fracture was stabilized with extension lock splint. Pathological fracture in patients with CLL is associated with hypercalcemia, Richter's transformation, or multiple myeloma. This patient exemplifies the fact that pathological fracture can be caused by CLL in the absence of hypercalcemia, Richter's transformation, or multiple myeloma and can be the initial presentation of CLL.